Teaching Structure with Molecular Visualization Tools. A Crash Course from Small Molecules to the HIV-1 Protease for Undergraduate Students - Paraskevi E Mpeza (Journal of Educational Sciences, 2021)
One of the challenges in the teaching of chemistry to students in higher education is their introduction to the visualization and molecular depiction software, deepening thus their understanding and creating new conceptions in the physical and biological sciences. This paper describes the implementation of a learning unit for 1st and 2nd semester undergraduate students (that were not previously exposed to molecular visualizations) in agricultural technology for chemistry and biochemistry courses respectively. A series of educational activities are presented beginning with the use of simple molecular models as plastic and wooden balls for atoms and sticks for bonds, to enhance the previous knowledge of the 2-D structural conformations. The students are introduced in depth to the theory of chemical bonding, molecular shapes, and polarity. This represents a continuum of increased complexity in inquiry-based learning, starting from simple molecules and ending with the exploration of the shape and function of a protein molecule, such as the human immunodeficiency virus (HIV)-1 protease; Thus easily leads to the study of the interactions between this protease and inhibitory drugs, via freely-available software tools. The gains in the students’ understanding and help for future courses and their career are analyzed.